2013
DOI: 10.1166/jbn.2013.1520
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Film Fabrication of Various Peptides on Neural Stem Cell Chip

Abstract: Modification of peptide on the electrode surface is very important issue for achieving valuable information from cell chip. In this study, various kinds of cysteine-containing peptide were fabricated on the electrode surface to enhance the electrochemical signals, cell spreading, and proliferation of rat neural stem cells. Different kinds of lysine-rich and RGD peptides were self-assembled on the gold nanoparticle modified ITO surfaces via strong Au-S chemical bond, followed by seeding neural stem cells (NE-4C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…9 Kim et al, have fabricated graphene oxide embedded nanofilms for biocompatible neuronal interfaces. 10 Bao et al, have confirmed the hemostatic potential and antimicrobial property of berberine loaded electrospun polycaprolactone nanofibrous membrane. 11 Delivered by Ingenta to: Rice University IP: 91.215.137.70 On: Sat, 11 Jun 2016 10: 45:46 Copyright: American Scientific Publishers Several biopolymers are used for the preparation of biocompatible films or membranes including chitosan, 12 alginate, 13 pectin, 14 gelatin, 15 carboxymethyl cellulose, 16 polyurethanes, 17 and hyaluronic acid.…”
Section: Introductionmentioning
confidence: 91%
“…9 Kim et al, have fabricated graphene oxide embedded nanofilms for biocompatible neuronal interfaces. 10 Bao et al, have confirmed the hemostatic potential and antimicrobial property of berberine loaded electrospun polycaprolactone nanofibrous membrane. 11 Delivered by Ingenta to: Rice University IP: 91.215.137.70 On: Sat, 11 Jun 2016 10: 45:46 Copyright: American Scientific Publishers Several biopolymers are used for the preparation of biocompatible films or membranes including chitosan, 12 alginate, 13 pectin, 14 gelatin, 15 carboxymethyl cellulose, 16 polyurethanes, 17 and hyaluronic acid.…”
Section: Introductionmentioning
confidence: 91%
“…To generate a gold-coated surface grafted with peptides, the gold-coated surface is immersed in aqueous alkanethiol solutions, which can be conjugated with bioactive peptides to generate SAMs, 91,[224][225][226][227][228] or the gold-coated surface is immersed with aqueous cysteine-containing peptide solution. 1,[229][230][231] 3.2.3.2. Carbodiimide reaction.…”
Section: Specific Reaction Between Functional Groups Of Materials Sur...mentioning
confidence: 99%